Menjawab Tuduhan Inkoherensi dari John Hick terhadap Konsep Dwinatur dalam Doktrin Inkarnasi Ortodoks - Yuliana, Fitri (Sekolah Tinggi Teologi SAAT, 2020)
Answering John Hick's Incoherence Allegations Against Dual-Nature Concept in the Orthodox Doctrine of Incarnation. In his writings, John Hick states that Christianity must rethink the claim to the divinity of Jesus as God the Son Incarnate. In his view, the dual nature in Jesus cannot be understood with common sense because the two natures contradict each other. As a way out, Hick offers the concept of mythologization which states that Jesus' incarnation as God the Son is a myth. To answer that, in this paper, in addition to basing her argument on the biblical statement, the author uses a combined logic approach: relativity thesis, natural kind concept, and divine preconscious model. With the method of relativity thesis, the author can point out the logic errors of incoherent accusations from Hick to the doctrine of the orthodox incarnation. Meanwhile, the natural kind concept approach can prove the coherence of the dual-natures concept in God the Son as an incarnation of God. The Divine preconscious model can provide a logical basis for the unity of the Person of Jesus with the two natures within Him, which do not contradict each other. With the combination of the three approaches, this paper presents a strong argument to prove that the doctrine of the orthodox incarnation is coherent. Thus, Christianity does not need to re-articulate the doctrine of the orthodox incarnation and also does not interpret the doctrine as a myth.